2011
DOI: 10.1016/j.amjcard.2011.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Adherence to Mediterranean or Low-Fat Diets in Medicated Secondary Prevention Patients

Abstract: Although the Mediterranean diet (MD) and the low-fat Therapeutic Lifestyle Changes Diet (TLCD) promote equivalent increases in event-free survival in secondary coronary prevention, possible mechanisms of such complete dietary patterns in these patients, usually medicated, are unclear. The aim of this study was to investigate the effects of the MD versus the TLCD in markers of endothelial function, oxidative stress, and inflammation after acute coronary syndromes. Comparison was made between 3 months of the MD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 25 publications
3
62
0
3
Order By: Relevance
“…In spite of this, endothelial functional improvement did not reach statistical significance (74) . A quantity of 10 -30 g nuts per d consumed by participants with either CVD risk or the metabolic syndrome also demonstrated no benefits on endothelial function (48,106) . Consumption of two doses (10 and 20 % of energy) of pistachios did not lead to a reduction in endothelial function (107) despite relatively high doses of up to 126 g/d consumed for 4 weeks.…”
Section: Effects Of Nut Consumption On Endothelial Vasodilator Functionmentioning
confidence: 99%
See 4 more Smart Citations
“…In spite of this, endothelial functional improvement did not reach statistical significance (74) . A quantity of 10 -30 g nuts per d consumed by participants with either CVD risk or the metabolic syndrome also demonstrated no benefits on endothelial function (48,106) . Consumption of two doses (10 and 20 % of energy) of pistachios did not lead to a reduction in endothelial function (107) despite relatively high doses of up to 126 g/d consumed for 4 weeks.…”
Section: Effects Of Nut Consumption On Endothelial Vasodilator Functionmentioning
confidence: 99%
“…A reduction in CRP was demonstrated in four studies with a portfolio diet containing either almonds (89,94,99) (14-30 g/d) or hazelnuts (30 g/d) (86) consumed for 4 weeks; one of these studies found an reduction equivalent to that observed with statin intake in the same individuals (89) . Beneficial improvements in inflammation observed in interventions which contained foods in addition to nuts (portfolio diet (88,89) or Mediterranean diet (47,48) ) may have been attributable to these other components. In contrast, Mediterranean diets in which walnuts (97) , mixed nuts (58,67) or pistachios (59) replaced olive oil demonstrated improvements in one or more of the inflammatory markers CRP, ICAM-1,VCAM-1 and IL-6, indicating that there may be some beneficial effect of nuts above that of other components of the Mediterranean diet.…”
Section: Effects Of Nut Consumption On Inflammatory Markersmentioning
confidence: 99%
See 3 more Smart Citations